Gender Identification Based on Ramus Mandibular Index and Gonial Index Through Panoramic Radiography in Javanese People - Icha Artyas Annariswati; Shintya Rizky Ayu Agitha; Eddy Hermanto (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Sex identification is an important first step in the forensic identification process because it can find a 50% probability of match in identifying individuals and can influence several other examination methods. The mandible is one of the facial bones that shows fairly clear sexual dimorphism. Mandibular morphometric analysis is often used in anthropology and forensic medicine to aid in sex identification. Material and Methods: A total of 62 panoramic radiographs consisting of 29 males and 33 females aged 15-25 years and of Javanese ethnicity were analyzed to determine the differences in the mandibular ramus index and mandibular gonial index variables between males and females using the Mann-Whitney U test. Results and Discussions: The results of the analysis showed significant differences in mandibular ramus height (p<0.05) and mandibular corpus length (p<0.05), with higher values in males than in females. Meanwhile, other variables such as the gonial angle, ramus width, anterior mandibular body height, and coronoid height did not show significant differences between the sexes (p>0.05). Conclusion: There are significant differences between the height of the mandibular ramus and the length of the mandibular body in males compared to females. Thus, the results of this study support previous findings that mandibular linear parameters can be used as reliable indicators in identifying.